Creating Common Ground: A framework for promoting interdisciplinarity - Goedereis, Eric A.; MacCartney, Danielle (Journal of Interdisciplinary Studies in Education, 2019)
Growing from an invited workshop on interdisciplinary learning the authors led at their institution’s annual faculty retreat, this manuscript offers a framework for encouraging faculty from diverse disciplines to consider and evaluate their teaching, scholarship, and service in interdisciplinary ways. In this paper, we present an application of a process that integrates Repko’s (2008) suggested criteria for interdisciplinarians, Doran, Miller, and Cunningham’s (1981) conceptualization of S.M.A.R.T. goals, and McCoy and Gardner’s (2012) five key social structural components, in order to further cultivate faculty members’ identities as interdisciplinarians. We conclude by summarizing participants’ comments in order to offer concrete examples of how the workshop yielded specific action plans for faculty members’ own interdisciplinarity within their teaching, research, and service activities. Taken together, this process challenges the traditional “silos” of academic work to help faculty reach across disciplinary boundaries. As such, this framework provides a roadmap for faculty and institutions interested in purposefully and meaningfully facilitating interdisciplinarity across a variety of academic settings.